Geometry optimisation of graphite energy degrader for proton therapy. (August 2020) - Oponowicz, E.; Owen, H.L.; Psoroulas, S.; Meer, D.
Highlights: Alternative energy degrader geometries for proton therapy facility. Single block offers higher transmission than multiple wedges degrader. Emittance calculations require beam core extraction from non-Gaussian distribution. Abstract: Introduction : Cyclotron-based proton therapy facilities use an energy degrader of variable thickness to deliver beams of the different energies required by a patient treatment plan; scattering and straggling in the degrader give rise to an inherent emittance increase and subsequent particle loss in the downstream energy-selection system (ESS). Here we study alternative graphite degrader geometries and examine with Monte-Carlo simulations the induced emittance growth and consequent particle transmission. Methods : We examined the conventional multiple-wedge degrader used in the Paul Scherrer Institute PROSCAN proton therapy system, the equivalent parallel-sided degrader, and a single block degrader of equivalent thickness. G4Beamline Monte-Carlo tracking of protons was benchmarked against measurements of the existing degrader for proton energies from 75 to 230 MeV, and used to validate simulations of the alternative geometries. Results : Using a careful calculation of the beam emittance growth, we determined that a single-block degrader placed close to the collimators of the ESS is expected to deliver significantly larger transmission, up to 17% larger at 150 MeV. At the lowest deliverable of 75 MeV there is still a clear improvement in beam transmission. Conclusions : Whilst dose rates are not presently limited on the PROSCAN system at higher energies, a single-block degrader offers the ability to access either lower energies for treatment or a larger dose rate at 75 MeV in case transmission optimisation is desired. Single-block degraders should be considered for the delivery of low-energy protons from a cyclotron-based particle therapy system.